2014
DOI: 10.1039/c4fo00095a
|View full text |Cite
|
Sign up to set email alerts
|

Oolong, black and pu-erh tea suppresses adiposity in mice via activation of AMP-activated protein kinase

Abstract: It is well known that tea has a variety of beneficial impacts on human health, including anti-obesity effects. It is well documented that green tea and its constituent catechins suppress obesity, but the effects of other types of tea on obesity and the potential mechanisms involved are not yet fully understood. In this study, we investigated the suppression of adiposity by oolong, black and pu-erh tea and characterized the underlying molecular mechanism in vivo. We found that the consumption of oolong, black o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 47 publications
3
52
0
Order By: Relevance
“…These results suggest that OTPs accelerated the metabolism of fatty acids in white adipose tissue. Previous studies have also found that consuming oolong tea (partially oxidized), black tea (full oxidized) and Pu-erh tea (oxidized and fermented) significantly decreased visceral fat levels without changing the body weight in mice [27,30]. These studies found that oolong tea, black tea and Puerh tea suppressed adiposity by activating AMPK.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These results suggest that OTPs accelerated the metabolism of fatty acids in white adipose tissue. Previous studies have also found that consuming oolong tea (partially oxidized), black tea (full oxidized) and Pu-erh tea (oxidized and fermented) significantly decreased visceral fat levels without changing the body weight in mice [27,30]. These studies found that oolong tea, black tea and Puerh tea suppressed adiposity by activating AMPK.…”
Section: Discussionmentioning
confidence: 58%
“…Compared with the results of previous studies, the inconsistency observed here might have been caused by the lower dose of OTPs or the shorter treatment time in our study. Most of the previous associated studies treated animals with Pu-erh tea extract for 8-12 weeks [27,28,30]. However, in our study, the rats were fed a high-fat diet containing OTPs for approximately 6 weeks.…”
Section: Discussionmentioning
confidence: 94%
“…Treatment with extracts of Oolong, black, or Pu-erh tea (in drinking fluid, similar to the experiment described above) was shown to activate AMPK in white adipose tissues [8]. Dietary supplementation of EGCG (0.2 or 0.5% in high-fat diet) to mice for 8 wk significantly decreased the mRNA levels of adipogenic genes, such as those for PPAR␥, CCAAT enhancer binding protein ␣, sterol regulatory element-binding protein-1c, lipoprotein lipase, and FAS in the epididymal white adipose tissues.…”
Section: In the Liver Skeletal Muscle And Adipose Tissuesmentioning
confidence: 81%
“…. The activation of AMPK by EGCG and different types of teas has been demonstrated in vivo and in vitro . It has been shown that at 1, 3, and 6 h after i.g.…”
Section: Molecular Mechanisms Of Action Of Tea Constituents In Body Wmentioning
confidence: 99%
“…And if all of the above is too much to take in, then without burning more neurons over this subject, one can be more practical and have a good jog followed up by a cup of black tea and a croissant, which is so much more pleasant (Wu et al 2014;Yamashita et al 2014) and simple delegate your intestines to work on the issue (Fang et al 2015;Mossenbock et al 2014).…”
mentioning
confidence: 99%